Some Geological Attractions Of Mount Chamah Area, Kelantan, Malaysia - Dony Adriansyah Nazaruddin; Hasimah Hassan; Ahmad Fadli Ahmad Sanusi (AENSI, 2013)
Mount Chamah (peak: 2171 m) is the highest point in the state of Kelantan, Malaysia and is one of the mountain peaks of the Main (Titiwangsa) Range, the “backbone” of Peninsular Malaysia. Preliminary identification and mapping of geological attractions in Mount Chamah area have been conducted by Universiti Malaysia Kelantan in collaboration with Kelantan State Forestry Department in 2011. Like other areas in the range, Mount Chamah area was also formed mostly of intrusive (granitic) rocks. Several main geological attractions in the area have been identified, such as Pichong River, Lata Pichong Waterfall, “Boat Rock” outcrop, and the morphologic panorama of the summit area.